Structuring Effect of the EU Framework Programmes in Estonia? The Case of Sociology - Tõnismann, Teele (Revue Gouvernance / Governance Review, 2018)
This article analyzes the extent that a European funding instrument, the Framework Programme (FP), has affected the structuring of sociologists’ project collaboration practices in a post-communist Estonia, which joined the EU in 2004. It is hypothesized that to better understand how the FP has structured the sociology discipline in Estonia, its usage should be studied in two distinct levels of academic context; the national and disciplinary levels. Science administrative elite have used the FP as a normative model for implementing national research funding policy reforms. In the case of sociologists, these reforms have engendered a partial auto-exclusion from competition for national grants perceived as highly competitive and resulted in an orientation towards commissioned contract funding both at a national and European level. This exposes the limited structuring effect of the FP in Estonia, a country otherwise considered an exemplary participant in EU programs.